Pengaruh Kesadaran Linguistik (Metalinguistic Awareness) terhadap Kemampuan Menulis Arab: Kajian Pustaka - Irfan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Learning Arabic, especially writing skills, is a complex challenge for both native and non-native speakers. Arabic has a structure and grammatical rules that are vastly different from other languages, such as Indonesian or English, and involves unique linguistic characteristics, such as right-to-left writing and the use of distinctive letters. One important component in language learning is Metalinguistic Awareness (MLA), which refers to the ability to understand and reflect on the elements of language, both orally and in writing. This study aims to examine the impact of MLA on Arabic writing skills, focusing on how MLA can help learners identify writing errors, organize sentence structures more accurately, and use appropriate vocabulary. This study employs a literature review approach to review the relevant literature on MLA and assess its impact on Arabic writing skills, at various levels of education, including elementary, secondary, and higher education. The findings from the literature review indicate that learners with higher levels of MLA tend to have better writing skills, especially in understanding complex sentence structures and correcting linguistic errors in their writing. However, despite these findings being supported by several studies, more empirical research is needed to specifically examine the application of MLA in the context of Arabic. Further research is also expected to develop more relevant MLA measurement instruments for Arabic and consider moderating factors that may affect its impact on writing skills.